Mullite corundum refractories on the basis of synthesized high-aluminous coal clay - Рыщенко, Александр Сергеевич; Рыщенко, Татьяна Дмитриевна; Питак, Ярослав Николаевич (Eastern-European Journal of Enterprise Technologies, 2012)
The processes of production of mullite corundum refractory material and high alumina chamotte are considered. The researches to obtaining of chamotte, selection of his optimal granulometric composition were carrying out